HALOGENS IN MICAS OF VOLCANIC ROCKS OF THE KURILE-KAMACHATKA ISLAND-ARC SYSTEM - Volynets O.N.; Bushyakov I.N.; Voronina L.K. (My University, 1989)
The role of volatiles in island-arc magma generation is widely discussed in the geologic literature. Two of the most important volatile mineralizers are fluorine and chlorine, whose principal accumulator minerals in igneous rocks include mica. The authors used the X-ray spectroscopic method to study the distribution of these elements in micas from 83 samples of volcanic rocks of the Kurile-Kamchatka island-arc system.